2021
DOI: 10.32479/ijeep.10671
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Demand and Supply of the Crude Oil Market During the Covid-19 Pandemic and Its Effects on the Natural Gas Market

Abstract: As a source of revenue for the state budget and a source of energy (particularly fuel) to drive various sectors of life, the oil and gas industry plays an important role in the Indonesian economy. The purpose of this study is to analyse the effect of crude oil prices on natural gas during the Covid19 Pandemic in Indonesia. The research method used is an explanatory method using the real price decomposition of crude oil introduced recently by Kilian ( 2009). This study develops four variables for the oil and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Their conclusion indicates a presence of asymmetric volatility in crude oil prices due to the spread of COVID-19. It is possible to notice a synergy with Indupurnahayu et al (2021) research, since the volatility in the natural gas price was not verified. Similarly, Qin et al (2020) said that as a consequence of the low demand, the oil prices dropped dramatically.…”
Section: The Covid-19 Impacts In the Oil And Gas Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Their conclusion indicates a presence of asymmetric volatility in crude oil prices due to the spread of COVID-19. It is possible to notice a synergy with Indupurnahayu et al (2021) research, since the volatility in the natural gas price was not verified. Similarly, Qin et al (2020) said that as a consequence of the low demand, the oil prices dropped dramatically.…”
Section: The Covid-19 Impacts In the Oil And Gas Industrymentioning
confidence: 99%
“…This drop is likely to be caused by measures of restriction in one hundred and eighty-seven countries that interrupted the mobility of its inhabitants, which culminated in a nine percent decrease in the global oil demand. Indupurnahayu et al (2021) analyzed the changes in the demand for crude oil in Indonesia during the COVID-19 pandemic, emphasizing its effects on the local natural gas market. As a conclusion, they found that COVID-19 caused the demand for oil and its derivatives to fall sharply.…”
Section: The Covid-19 Impacts In the Oil And Gas Industrymentioning
confidence: 99%
“…Over the last ten years, new factors have affected the behavior of oil prices. Some of these factors have a direct impact, such as the COVID-19 global lockdown that obviously reduced the demand on oil [1], which caused a historical futures price as, on 20 April 2020, the price of WTI-MAY 2020 futures contract closed at −37.68 per barrel [2]. Other factors have an indirect impact, such as the growing issue of climate change, which results in increasing antipathy towards oil among investors.…”
Section: Introductionmentioning
confidence: 99%